(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Developmental delays in early childhood significantly affect learning capacity, behavior, and long-term functional outcomes. Early childhood intervention (ECI) programs play a crucial role in improving developmental skills by addressing delays during the period of maximum brain plasticity. Methodology: This cross-sectional, questionnaire-based study was conducted among 41 children referred for early intervention and skill development at Shrivastava Clinic, Chhindwara, Madhya Pradesh, with data analyzed in the Department of Paediatrics, Sree Mookambika Institute of Medical Sciences, Kulasekharam. The study period was from March 2025 to February 2026. Developmental assessment was performed using the Denver Developmental Screening Test-II (DDST-II) and Madras Developmental Programming System (MDPS). Data were analyzed using descriptive statistics and independent t-test to compare gender differences across developmental domains. Results: Developmental delays were most common in language (71%) followed by fine motor (78%), personal-social (54%), and gross motor domains (24%). Global developmental delay was observed in 30 children. Significant gender differences were noted in gross motor (p<0.05), language (p<0.05), and personal-social development (p<0.05), while fine motor development showed no significant difference. Post-intervention assessment demonstrated improvement in multiple developmental domains. Conclusion: Early childhood intervention programs significantly improve learning capacities and developmental outcomes in children with developmental delays. Early identification and structured intervention are essential for optimal neurodevelopmental progress.